2022
DOI: 10.1002/jca.22036
|View full text |Cite
|
Sign up to set email alerts
|

Failure of double filtration plasmapheresis to treat severe pemphigus vulgaris: A case report

Abstract: Pemphigus vulgaris (PV) is a chronic, mucocutaneous, autoimmune bullous disease. Double filtration plasmapheresis (DFPP) may be effective when PV fails to be controlled by conventional corticosteroid treatment. The patient was a 64-year-old man with erythema, blisters, and erosions on his head, face, mouth, trunk, limbs, and scrotum for over a month. He was diagnosed with severe PV, and the original rash area continued to expand after treatment with systemic corticosteroids, immunosuppressants, and intravenous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The pathogenesis of anti-AChR antibody overshoot is thought to lie in an increase in B-cells in the peripheral blood lymphocyte population, activation of memory B-cells, and a reduction in antibody feedback inhibition due to a transient reduction in antibodies during plasma exchange [ 6 , 7 ]. A previous study of pemphigus vulgaris reported an overshoot of the anti-Dsg1 and anti-Dsg3 antibodies following a plasma exchange, which occurred within the first two weeks after a plasma exchange possibly owing to the production of autoantibodies by pathogenic B lymphocytes [ 8 ]. A similar mechanism may have been at work in the present cases of anti-AChR antibody overshoot following efgartigimod treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The pathogenesis of anti-AChR antibody overshoot is thought to lie in an increase in B-cells in the peripheral blood lymphocyte population, activation of memory B-cells, and a reduction in antibody feedback inhibition due to a transient reduction in antibodies during plasma exchange [ 6 , 7 ]. A previous study of pemphigus vulgaris reported an overshoot of the anti-Dsg1 and anti-Dsg3 antibodies following a plasma exchange, which occurred within the first two weeks after a plasma exchange possibly owing to the production of autoantibodies by pathogenic B lymphocytes [ 8 ]. A similar mechanism may have been at work in the present cases of anti-AChR antibody overshoot following efgartigimod treatment.…”
Section: Discussionmentioning
confidence: 99%